Virtual Project Management: Evaluation of an e-Learning Environment - Pagano, Rosane; Blair, Garry (Proceedings of the ... European conference on e-learning (Online), 2014)
Project Management is a multi-disciplinary subject area that covers a large knowledge base. More important, a deeper understanding of this area is, to a great extent, dependent on practice-based methods of learning, beyond the necessary assimilation of theory. This can pose some challenges to the delivery of higher education programmes in this area. Simulation could be the way forward as a means of replicating a 'live' project environment without the associated risks and resource issues. This paper reports on the value of learning by experimentation in project management education through the use of computer simulation in order to virtually re-create the dynamics of a project environment. The learners in this study were post-graduate students at a UK university. The simulation software used to create the virtual environment reproduces 'real' project complexity in a user-friendly mode, and it is normally used for the development of professional managers. The objectives of the study were to assess, for the subject student group, the following: (1) if the learner's perceived ability to apply project management knowledge was greater after the simulation experience; (2) if the increase in the learner's perceived ability to apply project management knowledge was greater for participants with little prior project work experience, after the simulation experience; (3) if the learner's team performance (team's simulation score) was smaller for learners experiencing difficulties with team interaction, than for those in a productive team interaction in a virtual environment. The study was carried out in two all-day simulation sessions. One addressed objectives 1 and 2 of the study. Here learners were put in teams of four or five to play the role of project manager and decision maker during the simulation, and they worked together face to face. The other session addressed objective 3, however here participants were geographically dispersed. An inter-institutional education program cooperation took place in order to form global teams. Learners from three universities located in three different countries composed each global team (two or three from each location formed a global team of six or seven participants). The focus of objective 3 was on investigating the potential challenges to performance of virtual team interaction, where cloud-based resources and digital communications were used. A more sophisticated version of the simulation software was employed in order to generate this distributed e-learning environment. The findings suggest that: overall the learners' perceived ability to apply project management knowledge was greater after the simulation experience; after the simulation experience, the increase in the learners' perceived ability to apply project management knowledge was greater for participants with little prior project work experience; the learners' team performance was not significantly less for learners experiencing difficulties with team interaction in the virtual environment.